Satellite Formation Flying Relative Dynamics, Formation Design, Fuel Optimal Maneuvers and Formation Maintenance - Wang, Danwei; Wu, Baolin; Poh, Eng Kee.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book systematically describes the concepts and principles for multi-satellite relative motion, passive and near passive formation designs, trajectory planning and control for fuel optimal formation maneuvers, and formation flying maintenance control design. As such, it provides a sound foundation for researchers and engineers in this field to develop further theories and pursue their implementations. Though satellite formation flying is widely considered to be a major advance in space technology, there are few systematic treatments of the topic in the literature. Addressing that gap, the book offers a valuable resource for academics, researchers, postgraduate students and practitioners in the field of satellite science and engineering.
Introduction -- Dynamic Models of Satellite Relative Motion around an Oblate Earth -- Passive and Periodic Satellite Formation Design around an Oblate Earth -- Nonlinear Optimization of Low-Thrust Trajectory for Satellite Formation -- Optimal Control for Satellite Formation Keeping -- Decentralized Control for Attitude Synchronization under Undirected Communication Topology -- Decentralized Control for Attitude Synchronization under directed Communication Topology.
Keywords: Control engineering; Robotics; Automation; Mathematical optimization; Calculus of variations; Aerospace engineering; Astronautics; Continuum mechanics; Control, Robotics, Automation; Calculus of Variations and Optimization; Aerospace Technology and Astronautics; Continuum Mechanics